(untitled) (European Journal of Health Research, 2019)
School cyberbullying isan increasingly worrying phenomenon in the classroom. The work that we present part of the research carried out in different schools in the Region of Murcia, where the CIE program (Coexistence and Emotional Intelligence) was applied during 5 weekly sessions, through a virtual classroom, the students collaboratively worked on the elements of Emotional intelligence to prevent and intervene in cyberbullying situations. There are two general objectives: to provide students with strategies to resolve conflicts and problems of coexistence and to check the effectiveness of the CIE program in reducing cyberbullying behaviors. Out of a total of 189 students from First and Second of ESO, between 11 and 16 years old (52.4% girls). The test-posttest methodology was used. The results confirm that the work and development of the elements of the CIE program have favored the reduction of detected cyberbullying behaviors, and also, it has a preventive action, by making students aware of this problem and the consequences it has. As conclusions, highlight that the application of the CIE program has shown that Emotional Intelligence is modifiable and teachable, facilitating adaptation and integration and that the program itself has been innovative and simple to apply.